KINERJA PENYULUH PERTANIAN LAPANG (PPL) DALAM PENGEMBANGAN BERAS ORGANIK MENUJU TERWUJUDNYA KABUPATEN SRAGEN SEBAGAI SENTRA BERAS ORGANIK - Bekti Wahyu Utami; Emi Widiyanti; Agung Wibowo (Universitas Sebelas Maret, 2008)
This research was conducted in Sragen Regency in which performance field extension workers very determining efficacy Sragen Regency as biggest organic sentra rice in the year 2010. So this research aimed at observing performance offield extensions workers spacious in rice organic program. In this research performance field extensions workers in organic rice program in Sragen Regency seeing from indicator such as reliability, responsiveness, assurance, emphaty and tangible:Proportion analysis test showed all value from indicator used give the result to accepted hypothesis zero (HO) and refused alternative hyphotesis (HI). It's mean research hypotesis inferential unprovable, so performance field extensions workers in organic rice program it 's bad/low.